Delimitation of Funga as a valid term for the diversity of fungal communities: the Fauna, Flora & Funga proposal (FF&F) - Francisco Kuhar; Giuliana Furci; Elisandro Ricardo Drechsler-Santos; Donald H. Pfister (IMA Fungus, 2018)
Abstract As public policies and conservation requirements for biodiversity evolve there is a need for a term for the kingdom Fungi equivalent to Fauna and Flora. This need is considered to be urgent in order to simplify projects oriented toward implemention of educational and conservation goals. In an informal meeting held during the IX Congreso Latinoamericano de Micología by the authors, the idea of clarifying this matter initiated an extensive search of pertinent terminologies. As a result of these discussions and reviews, we propose that the word Funga be employed as an accurate and encompassing term for these purposes. This supports the proposal of the three Fs, Fauna, Flora and Funga, to highlight parallel terminology referring to treatments of these macrorganism of particular geographical areas. Alternative terms and proposals are acknowledged and discussed.